THU0518 Characteristics, Outcomes, and Predictors of Complementary and Alternative Medicine use in Patients with Rheumatoid Arthritis. (23rd January 2014) - Choi, C.-B.; Sung, Y.-K.; Cho, S.-K.; Yoo, D.-H.; Lee, S.-S.; Lee, J.; Kim, J.; Lee, H.-S.; Kim, T.-H.; Yoon, B. Y.; Yoo, W.-H.; Choe, J.-Y.; et al.
Abstract : Background: Use of complementary and alternative medicine (CAM) is not uncommon in patients with rheumatoid arthritis (RA), but patient characteristics and the factors influencing and predicting its use is not well known. Objectives: We aimed to assess the characteristics and outcomes of CAM in patients with RA and to analyze the predicting factor for its use. Methods: A total of 5, 360 RA patients from the KORONA (Korean Observational Study Network for Arthritis) prospective multicenter cohort were assessed for use of CAM and characteristics including age, sex, disease duration, delay in diagnosis, family history, comorbidities, socioeconomic status, fatigue, sleep, pain, exercise, smoking, HAQ, EQ-5D, DAS28, medication, radiographic damage, surgery, and adverse events. Multiple logistic regression was used to analyze the predicting factors for CAM use. Results: Of the 5, 360 patients, 2, 468 (46.0%) patients responded that they have used CAM. Acupuncture was most common (73.3%) followed by herbal medicine (60.4%), moxibustion (30.7%), bee venom (19.1%), others (7.7%), and placenta injection (3.9%). Female used CAM significantly more and CAM users were significantly younger at onset (p<0.01), had longer disease duration (p<0.01), more family history (p=0.02), lower income (p<0.01), and lower education status (p<0.01). CAM users reported significantly more fatigue (p<0.01), more sleep disturbance (p<0.01), more pain (p<0.01), worse general condition (p<0.01), higher HAQ score (p<0.01), and lower EQ-5D score (p<0.01). They also had significantly higher disease activity (p<0.01, more use of steroids (p<0.01) and NSAIDs (p<0.01), had more radiographic damage (p<0.01), underwent more surgery (p<0.01), and had more adverse events (p<0.01). One or more problem in any of the dimensions of EQ-5D was significantly associated with the use of CAM. Factors significantly predicting the use of CAM were female gender (OR, 95%CI, 1.71, 1.30-2.45), older age, steroids (1.49, 1.29-1.72), adverse events (1.43, 1.26-1.63), radiographic damage (1.40, 1.21-1.62), regular exercise (1.35, 1.19-1.53), surgery (1.31, 1.10-1.55), high income (1.30, 1.06-1.60), and high DAS28 (1.07, 1.07-1.15). Conclusions: Patients with higher disease activity and lower health-related quality of life and higher functional disability used CAM significantly more frequently. Acknowledgements: This study is supported by a grant from the Korea Healthcare Technology R&D Project, Ministry of Health and Welfare, Republic of Korea (A102065). Disclosure of Interest: None Declared